2005
DOI: 10.1242/jeb.01493
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary fatty acid composition on depot fat and exercise performance in a migrating songbird, the red-eyed vireo

Abstract: SUMMARY Most migrating birds accumulate lipid stores as their primary source of energy for fueling long distance flights. Lipid stores of birds during migration are composed of mostly unsaturated fatty acids; whether such a fatty acid composition enhances exercise performance of birds is unknown. We tested this hypothesis by measuring metabolic rate at rest and during intense exercise in two groups of red-eyed vireos, a long-distance migratory passerine, fed either a diet containing 82% unsatura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

8
90
6

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 106 publications
(105 citation statements)
references
References 47 publications
8
90
6
Order By: Relevance
“…These FAs can be elongated to longchained, highly unsaturated PUFAs. These are especially relevant to study in the urbanization context due to their involvement in the regulation of physiological processes, such as cell membrane fluidity and transmembrane molecular movements, cardiac function, brain development, and immune responses (e.g., Hazel, 1995;Larsson et al, 2004;Pierce et al, 2005;Ben-Hamo et al, 2011;Hulbert and Abbott, 2012). Indeed, a recent study on great tits (Parus major) demonstrated that genes encoding enzymes responsible for biosynthesis of longchain PUFAs were differentially expressed between urban and rural individuals, although the factors underlying this habitatspecific difference, and the resulting physiological consequences, were not determined (Watson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These FAs can be elongated to longchained, highly unsaturated PUFAs. These are especially relevant to study in the urbanization context due to their involvement in the regulation of physiological processes, such as cell membrane fluidity and transmembrane molecular movements, cardiac function, brain development, and immune responses (e.g., Hazel, 1995;Larsson et al, 2004;Pierce et al, 2005;Ben-Hamo et al, 2011;Hulbert and Abbott, 2012). Indeed, a recent study on great tits (Parus major) demonstrated that genes encoding enzymes responsible for biosynthesis of longchain PUFAs were differentially expressed between urban and rural individuals, although the factors underlying this habitatspecific difference, and the resulting physiological consequences, were not determined (Watson et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, a ratio above 3 is considered to induce not only inflammation, but also pro-oxidant production, thereby potentially further increasing oxidative stress in urban-dwelling animals (Simopoulos, 2002;Kiecolt-Glasera et al, 2013). Because the immune system responds to pollution (Romieu et al, 2008;Isaksson, 2015, and references therein), the dietary FA composition, and resultant FA compositions of blood and tissues (Austin, 1993;Pierce et al, 2005;McCue et al, 2009;BenHamo et al, 2011), can play a significant role on birds' health in the urban environment. In addition, long-chain PUFAs are themselves sensitive to oxidative stress by being susceptible to lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…In humans, fatty acids (FAs) are the major fuel for low to moderate intensity exercises with muscular triacylglycerides (intramuscular triacylglycerides, IMTG) as well as total muscular lipids (intramuscular lipids, IML) increasing as the percentage of body fat increases (Hoeks et al, 2006;Hulver et al, 2003;van Loon et al, 2001). During long-distance flights, stored IMTG also serves as the primary fuel source for birds (McWilliams et al, 2004), with the selective mobilization of specific lipids from adipocytes an important step in this process (Pierce et al, 2005;Price et al, 2008). Specifically, utilizing n-3 polyunsaturated fatty acids (PUFAs) increased the aerobic capacity during long-distance migration in some bird species (Maillet and Weber, 2006;Pierce et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…During long-distance flights, stored IMTG also serves as the primary fuel source for birds (McWilliams et al, 2004), with the selective mobilization of specific lipids from adipocytes an important step in this process (Pierce et al, 2005;Price et al, 2008). Specifically, utilizing n-3 polyunsaturated fatty acids (PUFAs) increased the aerobic capacity during long-distance migration in some bird species (Maillet and Weber, 2006;Pierce et al, 2005). It has been suggested that the total amount of stored unsaturated fats may play an important role because they are more easily transported from adipose stores to the muscle during exercise as well as having higher whole-organism oxidation rates (Leyton et al, 1987).…”
Section: Introductionmentioning
confidence: 99%
“…Likewise, the nutrient composition of arthropods and fruits can vary spatially and temporally (Johnson et al 1985, Stiles 1993, Papon et al 2000, Mayntz and Toft 2001, and Bairlein (1998) showed that diets varying in their nutrient components have significant effects on mass gain in captive migrants. Moreover, the nutrient content of diets can affect composition of deposited fat, which can, in tum, affect physiological performance (Pierce et al 2005). If a bird cannot locate preferred food types, because of being in the "wrong" habitat or because of a lack of suitable habitat, its ability to successfully complete migration in a timely manner may be compromised.…”
Section: Introductionmentioning
confidence: 99%